La escritura con el cuerpo como una inversion de la dominacion masculina en "Novela negra con argentinos" (1990) y "La travesia" (2001) de Luisa Valenzuela - Cardona Nunez, Nohora Viviana (University of Ottawa (Canada), 2008)
The objective of this Master's thesis is to analyze how female characters are represented in the Argentinean Luisa Valenzuela's novels Novela negra con argentinos (1990) and La travesia (2001), and the way in which these characters, through the writing process, move forward in their awareness development and in the elaboration of a discourse that proposes an inversion to male domination. The introduction and theoretical framework explain both the objectives and the theoretical tools utilized throughout the thesis chapters: the first chapter develops the analysis of Novela negra con argentinos, emphasizing the concept of what the novel's main character calls writing with the body. An attempt is made to solve the questioning on whether it is possible to consider writing with the body within non-female aesthetics. The androgenisation process of Valenzuela's characters is also analyzed as a strategy that allows for questioning the roles that have traditionally been assigned to men and women. This strategy is also an attempt to bring closer two aesthetics that appear as conflicting in the text: the female discourse of writing with the body, and the male logocentric discourse. The second chapter focuses on the analysis of La travesia ; a novel that is considered as an adult Bildungsroman. This part shows how awareness through memory allows the main character to develop some strategies that make it possible for her to rebel against the patriarchal system. Such awareness becomes evident in the manner in which she begins to relate to men; as well as in finding a way of writing in which she has ceased to please the male Otherness that has alienated her for years. That way of writing gives her access to a new symbolic order in which gender relations appear more equitable. The last chapter presents the conclusions of this work on the Argentinean author who, through her essays and creative production, denounces the female oppression situation, as one of her structural central themes; as well as her proposals to promote liberation from such oppression.
Keywords: Literature, Latin American.